Eficacia bactericida in vitro de la superficie de cobre sobre pseudomonas aeruginosa intrahospitalaria en comparación con acero inoxidable - Asmat Marines, Ingrid Emperatriz (2017)
Objective: To evaluate the In Vitro bactericidal efficacy of the copper surface on intrahospital Pseudomonas aeruginosa compared to stainless steel. Materials and methods: We used an intrahospital strain, with metal surfaces of 1cm2 of stainless steel (control group) and copper (experimental group); 17 interventions were performed in each group. The bactericidal effect and bacterial adherence was determined according to the amount of Colonized Forming Units (CFU) present after exposure to metals. The mean comparison test, using the T student distribution with a significance level of 5% (p <0.05). Results: A measure of 6302,2 CFU / mL was obtained as results for the control group, which was similar to the inoculation; for the experimental group was 384 CFU / mL showing that copper has bactericidal effect compared to austenitic stainless steel. Bacterial adherence was determined through the CFU count, it was obtained a mean of 6080 CFU / ml for the control group and no CFU was found in the experimental group. Conclusions: The present work concludes that the copper surface has bactericidal effect In Vitro on intrahospital Pseudomonas aeruginosa, in contrast to the stainless steel surface in which they remained viable